Space, place and educational settings - Freytag, Tim; Lauen, Douglas L.; Robertson, Susan (Knowledge and space, 2022)
Chapter 1. Space, Place, and Educational Settings: An Introduction -- Chapter 2. Knowledge Society, Educational Attainment, and the Unequal City: A Sociospatial Perspective -- Chapter 3. Educational Inequality and Urban Development: Education as a Field for Urban Planning, Architecture and Urban Design -- Chapter 4. Bringing the Full Picture Into Focus: A Consideration of the Internal and External Validity of Charter School Effects -- Chapter 5. Neighborhood Effects, the Life Course, and Educational Outcomes: Four Theoretical Models of Effect Heterogeneity -- Chapter 6. Space, Marginality, and Youth in Urban Spaces: Pedagogical Practices in the Quartieri Spagnoli -- Chapter 7. Fragmented Geographies of Education: Institutions, Policies, and the Neighborhood -- Chapter 8. When School Comes to Community: Considering the Socioethnic Environment in Educational Reform for Gypsy Populations in a French City -- Chapter 9. Bringing the Local Back In: How Schools Work Differently in Different Neighborhood Contexts -- Chapter 10. Setting Aside Settings: On the Contradictory Dynamics of “Flat Earth”, “Ordinalization” and “Cold Spot” Education Governing Projects.